Analisis Penerapan Prinsip Tata Kelola yang Baik Pada Badan Usaha Milik Desa (BUMDES) Citra Mandiri Ketapang Banyuwangi - Wilujeng, Sri (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2024)
This research aims to determine and describe the Analysis of Good Governance Implementation in the Village-Owned Enterprises (BUMDes) Citra Mandiri in Ketapang Village, Kalipuro Sub-District, Banyuwangi Regency. This study uses a qualitative approach conducted intensively and comprehensively. The research sources use primary and secondary data. The results of the research are; (1) Planning: The planning carried out by BUMDes is highly coordinated and directed, serving as a guide in forming good governance; (2) Organizing: BUMDes Citra Mandiri has structured a formal structure and implemented hierarchy by existing duties, organizing correctly; (3) Actuating: The leadership of the Chairman of BUMDes Citra Mandiri in implementing and mobilizing existing resources has a significant impact on the behavior of individuals involved in achieving both quantitative and qualitative performance; (4) Controlling: BUMDes Citra Mandiri has implemented a monitoring process as an integral part, especially in the application of good governance in BUMDes Citra Mandiri. However, there is a need for improvement in building attachment, particularly in terms of a sense of ownership or awareness between human resources in BUMDes Citra Mandiri and the Ketapang Village Government.The importance of management processes and functions: planning, organizing, actuating, and controlling in addressing issues in the application of good governance principles in BUMDes Citra Mandiri, Ketapang Village, Kalipuro Sub-District, Banyuwangi Regency.